1995
DOI: 10.1302/0301-620x.77b6.7593101
|View full text |Cite
|
Sign up to set email alerts
|

The conservative treatment of complete tears of the anterior cruciate ligament in skeletally immature patients

Abstract: We describe the results of conservative treatment for complete midsubstance tears of the anterior cruciate ligament (ACL) in 18 skeletally immature patients, followed for a minimum of 36 months. Six patients had an ACL reconstruction during the follow-up period and were assessed immediately before their operation. The average time from initial injury to evaluation was 51 months. All patients had symptoms when reviewed. The modified Lysholm knee score showed one excellent result, one good, eight fair, and eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
1
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(185 citation statements)
references
References 26 publications
3
173
1
8
Order By: Relevance
“…McCarroll et al [26] found in 38 patients with ACL injuries followed for 4.2 years that 27 developed signs of meniscal injury and 37 of 38 had instability symptoms. Mizuta et al [27] presented similar results in 18 patients managed non-operatively. At 36 month follow-up 17 complained of instability, all 18 complained of pain and only 1 returned to previous activity levels.…”
Section: Natural History Of the Acl Deficient Kneementioning
confidence: 68%
“…McCarroll et al [26] found in 38 patients with ACL injuries followed for 4.2 years that 27 developed signs of meniscal injury and 37 of 38 had instability symptoms. Mizuta et al [27] presented similar results in 18 patients managed non-operatively. At 36 month follow-up 17 complained of instability, all 18 complained of pain and only 1 returned to previous activity levels.…”
Section: Natural History Of the Acl Deficient Kneementioning
confidence: 68%
“…Our study population confirms the variability in treating skeletally immature patients with a ruptured ACL. Mizuta et al reported on 18 skeletally immature patients who were treated conservatively [20]. All 18 patients had symptoms of instability and complained of pain, and only 1 returned to the previous level of athletic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the documentation of ACL injuries in skeletally immature patients has significantly increased during the past decade [1-5, 7, 8, 10-12, 16, 19, 21, 23, 24]. Non-reconstructive treatment often leads to poor results, especially concerning sports activity and further meniscal and chondral injuries [20,21]. Many surgical treatment options have been introduced, including primary repair and reconstruction, using both extra-articular as well as intraarticular procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, bracing, activity modification, and physical therapy were used with satisfactory short term results [32][33][34]. However, more recent reports of increased risk of subsequent surgery for meniscal and chondral pathology has shifted this paradigm [34][35][36].…”
Section: Nonoperativementioning
confidence: 99%
“…Instead, bracing, activity modification, and physical therapy were used with satisfactory short term results [32][33][34]. However, more recent reports of increased risk of subsequent surgery for meniscal and chondral pathology has shifted this paradigm [34][35][36]. Still more studies have shown that nonoperative treatment of ACL injuries can lead to chronic instability and poor outcomes, with fewer athletes able to return to their sport at the same or higher level than in those undergoing reconstruction [35,37].…”
Section: Nonoperativementioning
confidence: 99%